The relationship between body mass index with quality of CPR compression in Nursing Students - Endiyono Endiyono; M. Hanif Prasetya Adhi; Ragil Setiyabudi (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2021)
Background: Coronary Heart Disease is one of the diseases that causes the most deaths in Indonesia. One of the causes of death from coronary heart disease is cardiac arrest. One of the help that can be given is CPR (Cardiopulmonary Resuscitation). CPR can be performed by ordinary people or trained personnel. The phenomenon that often occurs is that when compression is performed, students are often not optimal in providing compression in terms of compression depth. The impact of poor quality CPR can cause death, economic, psychological, social, and length of treatment.Objectives: This study aims to determine the relationship between Body Mass Index (BMI) and the Quality of Cardiac and Lung Resuscitation Compression in Nursing Students.Method: This study uses a descriptive analytic research, with an observational method using a cross sectional design using a total sampling of 46 respondents.Result: Based on the results of Fisher's Exact test, p-value < (0.001 < 0.05) was obtained so that there was a relationship between student BMI and quality into compression. The quality of nurses' chest compressions in performing chest compressions is lacking, even though some nurses have had cardiopulmonary resuscitation training. Someone who has a high and low BMI in the hospital, it was found that when doing chest compressions the patient gets tired quickly, a high BMI is difficult to do chest compressions when getting into bed.Conclusion: Body Mass Index can improve the quality of student compression in cardiopulmonary resuscitation. BMI indirectly plays an important role in the performance of nurses in order to provide optimal cardiopulmonary resuscitation.